The Complete Genome Sequence of the Fish Pathogen Tenacibaculum maritimum Provides Insights into Virulence Mechanisms - Pérez-Pascual, David; Lunazzi, Aurelie; Magdelenat, Ghislaine; Rouy, Zoe; Roulet, Alain; Lopez-Roques, Celine; Larocque, Robert; Barbeyron, Tristan; Gobet, Angélique; Michel, Gurvan; Bernardet, Jean-François; Duchaud, Eric (Frontiers in Microbiology, 2017)
Tenacibaculum maritimum is a devastating bacterial pathogen of wild and farmed marine fish with a broad host range and a worldwide distribution. We report here the complete genome sequence of the T. maritimum type strain NCIMB 2154T. The genome consists of a 3,435,971–base pair circular chromosome with 2866 predicted protein-coding genes. Genes encoding the biosynthesis of exopolysaccharides, the type IX secretion system, iron uptake systems, adhesins, hemolysins, proteases and glycoside hydrolases were identified. They are likely involved in the virulence process including immune escape, invasion, colonization, destruction of host tissues and nutrient scavenging. Among the predicted virulence factors, type IX secretion-mediated and cell-surface exposed proteins were identified including an atypical sialidase, a sphingomyelinase and a chondroitine AC lyase which activities were demonstrated in vitro.